The Utilization of GeoGebra in Mathematics Education on Students' Conceptual Understanding: A Systematic Literature Review - Robiatul Adawiah; Aulia Aulia; Lutfiatussolihah Lutfiatussolihah; Gunawan Gunawan; Nina Nisrina (Indonesian, 2025)
Students' understanding of mathematical concepts remains relatively low, necessitating technological innovations in education to address this issue. A promising solution is the integration of GeoGebra as an interactive learning tool. This study aims to evaluate the effectiveness of GeoGebra in mathematics education regarding students' conceptual understanding through a systematic literature review. Utilizing a Systematic Literature Review (SLR) method with a qualitative descriptive approach, data were sourced from scientific articles in national and international journals via Google Scholar, ProQuest, and Springer Nature databases published between 2016 and 2025. The literature selection followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, resulting in 16 articles that met the inclusion criteria. The findings demonstrate a consistent pattern wherein the utilization of GeoGebra significantly enhances students' conceptual understanding compared to conventional methods. This improvement is evidenced by increased average learning outcome scores, higher post-test than pre-test results, and statistically significant differences between the GeoGebra and conventional groups. Furthermore, GeoGebra proves effective across various educational levels and mathematical topics due to its capacity to visualize abstract concepts dynamically and interactively.